An Energy Gap for Complex Yang-Mills Equations - Huang, T. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
We use the energy gap result of pure Yang-Mills equation [Feehan P.M.N., Adv. Math. 312 (2017), 547-587] to prove another energy gap result of complex Yang-Mills equations [Gagliardo M., Uhlenbeck K., J. Fixed Point Theory Appl. 11 (2012), 185-198], when Riemannian manifold X of dimension n≥2 satisfies certain conditions.